An analysis of the role played by Non Governmental Organizations (NGOs) in Zimbabwe’s democratization process. a case of Zimbabwe Civic Education Trust (ZIMCET) - Chipunga, Charity J. (Midlands State University, 2020)
This thesis makes an assessment of the role played by NGOs in Zimbabwe’s democratization process. NGOs around the globe have been perceived as partners for development and key players in the field of democracy. Due to their close link to the grassroots citizens they are considered as strategic partners as they resemble the will of the people from below thus promoting democratic values. However this has not been the case in Zimbabwe, the relationship between the government and the NGOs has been described by many as antagonist and some have argued that this is the reason why Zimbabwe’s democratization process has been temporized over the years. Thus the main aim of this research was to understand the work that NGOs have contributed to the advancement of democracy in Zimbabwe and the effectiveness of this work. To ascertain the level of effectives of the work of the NGOs this dissertation provides an intense understanding of the activities, projects and programmes of the NGOs and how they try to compliment the government’s efforts. NGOs in Zimbabwe in an effort to encourage active and meaningful citizen participation have been involved in the protection of human rights, monitoring the electoral cycle, peace building and conflict resolution. It also examines how NGOs interact with other stakeholders other than the government in issues concerning democracy. The dissertation also sought for possible avenues of cooperation between the NGO sector and the government. It is through this research that recommendations on how the government and NGOs can work together more effectively and how the NGOS working in the field of democracy can improve their work are proffered. The dissertation makes use of both primary and secondary data however dwelling much on interviews, questionnaires, newspaper articles and personal observations.